2009
DOI: 10.1186/1471-2377-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya disease: A clinical spectrum, literature review and case series from a tertiary care hospital in Pakistan

Abstract: BackgroundMoyamoya is a rare cerebrovascular disease of unknown etiology. The data on moyamoya disease from Pakistan is sparse. We report a case series of 13 patients who presented with moyamoya disease to a tertiary care hospital in Pakistan with a national referral base.MethodsWe conducted a retrospective review of thirteen patients who presented to The Aga Khan University and diagnosed with "Moyamoya Disease" during the period 1988 – 2006. These patients were identified from existing hospital database via I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…All patients in the studies conducted by Singhi et al 21 The only patient with hemorrhagic stroke presented with basal ganglia bleed with intraventricular hemorrhage. Duan et al 26 had 2.3% incidence of hemorrhagic stroke in the pediatric population, whereas Shoukat et al, 19 Srivastava et al 23 and Singhi et al 21 had none. Historically, bleeding has been attributed to rupture of fragile collateral vessels associated with moyamoya as progressive stenosis of the ICA occurs.…”
Section: Clinical Profilementioning
confidence: 99%
“…All patients in the studies conducted by Singhi et al 21 The only patient with hemorrhagic stroke presented with basal ganglia bleed with intraventricular hemorrhage. Duan et al 26 had 2.3% incidence of hemorrhagic stroke in the pediatric population, whereas Shoukat et al, 19 Srivastava et al 23 and Singhi et al 21 had none. Historically, bleeding has been attributed to rupture of fragile collateral vessels associated with moyamoya as progressive stenosis of the ICA occurs.…”
Section: Clinical Profilementioning
confidence: 99%
“…One small mixed series (Shoukat et al, 2009) of seven patients under age 12 years and six over age 12 reported EEGs in six patients: four with diffuse slowing and two with epileptiform activity, but the age of the patients receiving EEGs was not specified. Similar observations were made in an Italian series of 27 pediatric and 7 adult cases with moyamoya.…”
Section: Introductionmentioning
confidence: 98%
“…There has not been much studied regarding moyamoya in our population as there are only two case series with a total of 17 patients, of which 10 were of less than 12 years of age [3, 4]. Few studies reported higher incidence of stroke in younger age group in our part of the world as compared to western population, which probably indicate underdiagnosis of moyamoya [5].…”
Section: Introductionmentioning
confidence: 99%